Wheelchair users’ experiences of access to healthcare in Western Cape Province, South Africa - Abrahams, Shaunelia Heidi (Stellenbosch : Stellenbosch University, 2024)
Thesis (MHumanRehabSt)--Stellenbosch University, 2024.